A Study on Upskilling and Reskilling in AI-Powered Roles in India - Vijimalar, R.; S V, Subhiksha; Ragila, A.Franklin; Regima, V. (Journal of Neonatal Surgery, 2025)
Artificial Intelligence (AI) is reshaping the employment landscape across sectors, necessitating continuous learning and adaptability. This study examines the importance of upskilling and reskilling for employees in AI-powered roles in India. With the rapid integration of automation, machine learning and data analytics, the workforce must acquire new digital competencies to remain relevant. This paper highlights the initiatives taken by the Indian government, private organizations and educational institutions to bridge the skill gap and explores challenges in implementing large-scale reskilling programs. The findings underscore that proactive investment in human capital and lifelong learning strategies is crucial to harness AI’s potential for inclusive economic growth..